Effect of Modified Cooking on Chemical Composition of Pulps from Eucalyptus globulus and Eucalyptus nitens - Rudine Antes; Olli Pekka Joutsimo (BioResources, 2014)
The effects of SuperBatch™ (SB), CompactCooking™ (CC), and Lo-Solids™ (LS) modified cooking processes on pulp properties of Eucalyptus globulus and Eucalyptus nitens were investigated. The syringyl/guayacil (S/G) lignin ratio in the wood of E. globulus was significantly higher (4.7) than that of E. nitens (3.5). From the brown stock pulps, the viscosity, total lignin, carbohydrate composition, acetone extractives, and hexenuronic acids were measured. For the same Kappa number level (17 ± 0.5), pulps from E. globulus needed lower H-factor. They also presented a higher brightness and more cooking rejects, independent of the cooking method. CC presented a slightly higher cooking yield and pulp viscosity compared to the other modified cooking methods. At the same Kappa number level, the pulps of E. nitens presented a greater amount of total lignin, whereas E. globulus presented a higher amount of hexenuronic acid content, independent of the cooking method.